Family practitioners' advice about taking time off work for lower respiratory tract infections: a prospective study in twelve european primary care networks - Godycki-Cwirko, M; Nocun, M; Butler, C; Little, P; Verheij, T; Hood, K; Fleten, N; Kowalczyk, A; Melbye, H (Public Library of Science, 2016)
Acute cough and lower respiratory tract infections (LRTIs) are one of the most important causes of lost working hours.to explore variation and predictors in family practitioners (FPs) advice to patients with LRTIs about taking time off work in different European countries.Prospective observational study in primary care networks in 12 countries, with multilevel mixed-effects binomial logistic regression.324 FPs recruited 1616 employed adults who presented to primary care with LRTIs. The proportion of patients advised to take time off work varied from 7.6% in the Netherlands to 89.2% in Slovakia, and of these, 88.2% overall were advised to stay off work for seven days or less. None of Finnish or Dutch patients were advised to take more than 7 days off, in contrast to 35.5% of Polish and 27.0% of Slovak patients. The strongest predictors of FPs' advice about time off work were: patient symptoms interfering with normal activities (OR 4.43; P<0.001), fever (2.49; P<0.001), patients feeling generally unwell (2.21; P<0.001), antibiotic prescribing (1.51; P = 0.025) and auscultation abnormality (1.50; P = 0.029). Advice to take time off was not associated with patient reported recovery.There is large variation in FPs' advice given to patients with LRTIs in Europe about taking time off work, which is not explained by differences in patients' reported illness duration, but might be explained by differences in regulations around certification and sick pay. Evidence based guidance for advising patients about taking time off work for this common condition is needed.